Isolasi DNA Jamur dari Tumbuhan Alpukat dengan Metode Spin Column - Alya Nabila; Yuni Ahda (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The advancement of molecular biology requires efficient nucleic acid extraction methods to overcome the complexity of biological samples. Fungi associated with avocado plants possess strong cell walls and the presence of host secondary metabolites that may potentially inhibit molecular analyses. This study aimed to isolate and evaluate the quantity and quality of fungal DNA from avocado plants using a combination of mechanical disruption (bead beating) and spin column-based purification. Fungal DNA was isolated using the Quick-DNA™ Fungal/Bacterial Miniprep Kit. Quantification using a NanoDrop spectrophotometer showed that DNA concentrations ranged from 1.7 to 139.1 ng/µL. Most samples yielded DNA concentrations above 50 ng/µL with A260/280 purity ratios ranging from 1.87 to 1.98. Mechanical disruption using beads in a lysis tube facilitated the breakdown of fungal cell walls, while the silica column effectively purified DNA and reduced contaminants that could potentially interfere with analysis. Therefore, the combination of bead beating and spin column methods effectively produced high-quality genomic DNA suitable for further molecular analyses, such as Polymerase Chain Reaction (PCR).